Advancing aphasia psychological care in Ireland: A participatory study with people with aphasia and clinicians - Molly X. Manning; Brian McClean; Libby Cunningham; Jolene Dervin; Marcia Ward; Aoife Carolan (PLoS ONE, 2026)
Background Aphasia increases the risk of mental health issues, yet psychological care for aphasia (APC) is not routinely available. Given the significant psychosocial impact, APC requires input from multiple disciplines and settings, and necessarily responds to a person’s needs, which shift over time. As a complex intervention, it is important that service providers, users, and policymakers are involved in developing effective and contextual implementation strategies. In this study, the aim was to meaningfully engage people with aphasia and inter-disciplinary aphasia clinicians to create a shared vision of ideal APC and to identify context-specific implementation considerations in Ireland. Methods A series of interdisciplinary clinician research workshops and parallel aphasia Public and Patient Involvement (PPI) meetings were convened. Participatory Learning and Action (PLA) tools and techniques supported inclusive research spaces; and discussions were scaffolded by constructs from the implementation science framework, Normalisation Process Theory (NPT). PPI contributors inputted into planning the clinician workshops and reviewed and commented on the discussion summaries. Results Key principles for APC and Ireland-specific implementation considerations were identified. These included the need for a unified vision, clear clinical roles and referral pathways, improved team structures and resources, clinician training, and active involvement of people with aphasia in APC design. Conclusions Through NPT and PLA informed workshops, people living with aphasia and clinicians generated ideas about how an interdisciplinary coordinated model of APC might be developed and implemented. The findings offer early guidance for developing coordinated, interdisciplinary APC in Ireland. The participatory implementation approach may be adapted to other conditions or contexts to support locally relevant intervention planning.